Institutional Optimization Strategy of Capital Investment Agency and One-Stop Integrated Service (Jurnal Bina Praja, 2019)
Licensing is one way for business actors to formalize business. Without licensing, businesses are unable to move to the formal sector and get a variety of benefits such as coaching programs, tax incentives and getting credit or capital assistance, especially from banks and legal guarantees. Nevertheless, business operators consider that licensing services are still not optimal. Business actors' complaints include inefficient and effective services caused by weak institutional aspects. Institutional improvement of the Capital Investment Agency and the One-Stop Integrated Service (DPMPTSP) to reach the prime point will have an impact on the ease of service and improve the investment climate. The main method used in this study is the Regulatory Impact Assessment (RIA) supported using Regulatory Mapping (Regmap) to determine the regulatory map that contributes to the institutional aspects of DPMPTSP. The results of the analysis revealed that the root cause of the weakness of DPMPTSP's institutions was the absence of DPMPTSP's institutional improvement program. The root causes of these problems contribute to some of the problems in optimizing DPMPTSP institutions such as the Standard Operational Procedure (SOP) that is not updated, the lack of competence of the implementing apparatus, the delay in anticipating changes in regulations of the central authority. Alternative corrective actions from the results of the analysis are the devolution of authority for licensing services, preparation of guidelines for Standard Procedure Norms Criteria (NSPK), institutional regulation updates, preparation of local regulations related to institutional implementation, SOP formulation of licensing services, placement of technical human resources, and development of infrastructure facilities.
Keywords: DPMPTSP; Licensing; Regulatory Impact Assessment (RIA)